Silver nanoparticle-decorated NiFe2O4/CuWO4 heterostructure electrocatalyst for oxygen evolution reactions - Kumar U.; Sanket K.; Mandal R.; Kumar De A.; Shrivastava A.; Behera S.K.; Sinha I. (My University, 2025)
In this work, Ag nanoparticles decorated with NiFe2O4/CuWO4 heterostructure were synthesized using the step-wise precipitation method. The influence of varying Ag loading on the NiFe2O4/CuWO4 heterostructure and its electrochemical OER performance was extensively studied in 1 M KOH electrolyte. The obtained LSV profile was analyzed to determine the overpotential, Tafel slope, and onset potential. The heterostructure with an optimal Ag loading of 5 wt% required the least overpotential (1.60 V vs. RHE) for generating a current density of 10 mA cm−2 with a lower Tafel slope of 44.5 mV dec−1, indicating its faster OER kinetics. Furthermore, the composite remained stable over a period of 24 hours with a minimum rise in the overpotential after the stability test. The enhanced OER performance of the as-prepared catalyst can be attributed to the presence of multiple metallic elements in the Ag-loaded NiFe2O4/CuWO4 composite, which created a diverse array of oxygen-vacant sites with varying reactivity, enhancing the charge-transfer kinetics; and thus contributing to the overall efficiency of OER. Therefore, optimizing the Ag concentration and engineering a microstructure represents an encouraging strategy for developing cost-effective catalysts for next-generation energy-conversion applications. © 2024 The Royal Society of Chemistry.